Criminalistics for the law enforcement officer - Califana, Anthony L.; Levkov, Jerome S. (McGraw-Hill, 1978)
This introductory text is directed toward police officers or other students of criminalistics; it describes all essential phases of forensic science. Mainly from a practical point of view, the book focuses upon the major areas in which the techniques if criminalistics contribute to the identification and apprehension of criminals, such as document examination, fingerprints, hair, blood, drugs, photography, and firearms investigation. The preservation and care of evidence is the first major consideration in a criminal investigation. Students are taught how to secure and protect the crime scene; photograph or otherwise document the entire scene; locate, collect, and preserve pertinent evidence. The essentials of fingerprinting -- lifting the prints from different surfaces, taking a suspect's fingerprints, and identifying various fingerprint patterns -